Pengaruh Value Added Capital Employed, Structural Capital Value Added dan Dewan Direksi Terhadap Kinerja Keuangan - Johny Subarkah (ITB AAS INDONESIA, 2021)
This study aims to determine the effect of added value capital employed, structural capital added value and the board of directors on financial performance. This research is a type of quantitative descriptive research. The population used in this study is the banking sector companies listed on the Indonesia Stock Exchange as many as 43 companies, while the research sample used is banking companies listed on the Indonesia Stock Exchange for the period 2017-2019 with the sampling technique used in this study is to using purposive sampling method. The criteria for the companies used as samples in the study are banking companies listed on the Indonesia Stock Exchange and have published their financial statements and annual reports for four consecutive years from 2017 to 2019 and companies that earn profits in their business, and have never experienced losses during the 2017-2019 period. Research testing using the F test, t test, and the coefficient of determination test (R2). The results showed that the Value Added of Capital Employed (VACA), Structural Capital Value Added (STVA) and the Size of the Board of Directors (DD) simultaneously had a significant effect on Financial Performance (ROA). Value Added of Capital Employed (VACA) has no effect on Financial Performance (ROA). Structural Capital Value Added (STVA) has a positive effect on Financial Performance (ROA). The size of the Board of Directors (DD) has a positive effect on Financial Performance (ROA). Adjusted R Square of 0.549 or 54.9%. This shows that the company's financial performance variable (ROA) of 54.9% explains the Intellectual Capital variable with its components namely Value Added of Capital Employed (VACA) and Structural Capital Value Added (STVA) and good corporate governance with the indicator used is Board Size. Directors, while the remaining 45.1% is explained or influenced by other variables that are not used in this study.